(untitled) (Texas Journal of Philology, Culture and History, 2024)
It is known that dialogic discourse can also be part of monologic speech. There are several types of it. Monological discourse is methodologically neutral and is directed from the third person to the second person. Sometimes in monologic discourse, the third person refers to himself and the second person. In addition, dialogic discourse is also found in monologic discourse. In this case, monologic discourse and dialogic discourse are given in relation to each other. In a conversational monologue, the speech is directed from the first person to the second person, drawing the addressee’s attention to the speech process